2015
DOI: 10.1093/gbe/evv151
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ParentalBos taurusandBos indicusOrigins on Copy Number Variation in Traditional Chinese Cattle Breeds

Abstract: Copy number variation (CNV) is an important component of genomic structural variation and plays a role not only in evolutionary diversification but also in domestication. Chinese cattle were derived from Bos taurus and Bos indicus, and several breeds presumably are of hybrid origin, but the evolution of CNV regions (CNVRs) has not yet been examined in this context. Here, we of CNVRs, mtDNA D-loop sequence variation, and Y-chromosomal single nucleotide polymorphisms to assess the impact of maternal and paternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
0
13
1
Order By: Relevance
“…Moreover, a copy-number deletion associated with reduced blood concentrations of hemoglobin, a characteristic of highaltitude adaptation in Tibetans, has been identified (Lou et al, 2015). CNV data have been used to analyze population relationships in some Chinese indigenous cattle breeds (Zhang et al, 2015a;Mei et al, 2019). However, to date, high-altitude adaptation analyses of genomic CNVs in Chinese indigenous cattle are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a copy-number deletion associated with reduced blood concentrations of hemoglobin, a characteristic of highaltitude adaptation in Tibetans, has been identified (Lou et al, 2015). CNV data have been used to analyze population relationships in some Chinese indigenous cattle breeds (Zhang et al, 2015a;Mei et al, 2019). However, to date, high-altitude adaptation analyses of genomic CNVs in Chinese indigenous cattle are limited.…”
Section: Introductionmentioning
confidence: 99%
“…CNVs markers are more effective as compared to SNPs markers, due to more genomic sequences, including gene structure changing and dosage, changing gene regulation, and recessive alleles exposing [2] . Recently, a number of studies confirmed CNVs regions in bovine genome that cover a number of genes related to environment adaptation [3] . CNVs regions have tendency to demonstrate breed`s history and their formation patterns [4] .…”
Section: Introductionmentioning
confidence: 99%
“…As we know, molecular markers are a reflection of genetic polymorphism at the DNA level directly, since the genetic variation of nucleotide sequence among different breeds. Researchers used mitochondrial DNA makers (Xue et al 2014), microsatellite of Y chromosome (Acosta et al 2013), and copy number variation (Zhang 2015;Xu et al 2016) widely to assess genetic diversity and population structure of domestic animal in previous studies. Currently, with the advent of effective and high-throughput technology, more detail assessment of population structure and admixture history of cattle were conducted.…”
Section: Introductionmentioning
confidence: 99%